(untitled) (Andamios, Revista de Investigación Social, 2024)
The objective of this article is to problematize female leadership in disaster risk management, as part of work networks with different levels of interest and incidence. Through ethnography, the gender perspective allows us to characterize these leaderships in the settlement of La Primavera (municipality of Barbosa - department of Antioquia, Colombia). Likewise, the social construction of risk allows discussing issues about vulnerability, resilience and participation of women in community settings translatable into alliances and/or conflicts, where female leaders go through empowerment, community resilience and the stimulation of local conflicts, to conclude that they are complex leaderships that invite to de-idealize the roles of women in these contexts.